G-Quadruplex Structures in the Human Genome as Novel Therapeutic Targets - Joanna Bidzinska; Graziella Cimino-Reale; Marco Folini; Nadia Zaffaroni (Molecules, 2013)
G-quadruplexes are secondary structures that may form within guanine-rich nucleic acid sequences. Telomeres have received much attention in this regard since they can fold into several distinct intramolecular G-quadruplexes, leading to the rational design and development of G-quadruplex‑stabilizing molecules. These ligands were shown to selectively exert an antiproliferative and chemosensitizing activity in in vitro and in vivo tumor models, without appreciably affecting normal cells. Such findings point to them as possible drug candidates for clinical applications. Other than in telomeres, G-quadruplexes may form at additional locations in the human genome, including gene promoters and untranslated regions. For instance, stabilization of G-quadruplex structures within the promoter of MYC, KIT, or KRAS resulted in the down-regulation of the corresponding oncogene either in gene reporter assays or in selected experimental models. In addition, the alternative splicing of a number of genes may be affected for a therapeutic benefit through the stabilization of G-quadruplexes located within pre-mRNAs. It is now emerging that G-quadruplex structures may act as key regulators of several biological processes. Consequently, they are considered as attractive targets for broad-spectrum anticancer therapies, and much effort is being made to develop a variety of ligands with improved G-quadruplex recognition properties. Quarfloxin, a fluoroquinolone derivative designed to target a G-quadruplex within ribosomal DNA and disrupt protein-DNA interactions, has entered clinical trials for different malignancies. This review will provide some hints on the role of G-quadruplex structures in biological processes and will evaluate their implications as novel therapeutic targets.